PENGARUH IKLAN DENGAN UNSUR HUMOR DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN: Studi Kasus Iklan Rokok Djarum 76 Versi Kontes Jin 2012 - Unggul Bima Sakti (ECONOMOS, 2022)
The COVID-19 pandemic has hit all over the world which has made markets sluggish and the impact of consumer culture has drastically reduced. Company leaders must be able to rack their brains in order to survive in the midst of a pandemic. Advertising or advertising in general is the main weapon in marketing products, so advertising must be creative and innovative. If the first impression on the advertisement is very good and can be accepted by potential consumers to influence purchasing decisions, then the advertisement means it is effective in attracting consumers, on the contrary if a product advertisement does not give an impression, it means that it is less effective in advertising a product and consumers are not interested. to buy the product. This study tries to explain the effect of advertising with elements of humor and price on consumer purchasing decisions. This study uses quantitative methods with survey research using a questionnaire as an instrument. The population in this study were the residents of the brondong and blimbing villages who had bought and seen the 2012 genie contest version of the Djarum 76 cigarette advertisement. This study drew samples using simple random sampling method (simple sample technique) with probability sampling technique. The data analysis technique used multiple linear regression technique. The results of this study indicate that all independent variables, namely Advertising with Humor, and Price have a positive influence on the dependent variable, namely consumer purchasing decisions.